RI 3337 Annual Report Of The Explosives Division, Fiscal Year 1936 ? Introduction (d2616de2-6769-4d2e-abd6-d5d906b4eff2) - Wilbert J. Huff (The National Institute for Occupational Safety and Health (NIOSH), 1937)
The Explosives Division of the United States Bureau of Mines makes certain laboratory and field investigations that deal with explosions, explosives, ignition, and combustion, together with many related problems, such as the cause and prevention of fires, and certain fundamental scientific questions bearing upon the determination of the chemical and physical mechanisms underlying some of the important phenomena encountered. Its work on explosives has been particularly directed toward determination of the chemical and physical characteristics of explosives designed for use in coal mines and in a more limited way to those used in metal mines, tunnels, quarries, and other engineering operations. This testing is handled by two units of the Explosives Division, as follows: